Young adults' perspectives on their psychosocial outcomes 16 years following childhood traumatic brain injury. Issue 3 (5th August 2014) - Rosema, S.; Muscara, F.; Anderson, V.; Godfrey, C.; Eren, S.; Catroppa, C.
Abstract : Purpose: – Childhood traumatic brain injury (CTBI) is one of the most common causes of mortality and disability in children and adolescents that impacts on neuropsychological, social and psychological development. A disruption of development in these areas often results in long-term problems with interpersonal relationships, participation in leisure and social activities and employment status. These social and psychological problems appear to persist longer in comparison to other functional consequences, although evidence is scarce. The purpose of this paper is to investigate social and psychological outcomes 15 years post-injury. Design/methodology/approach: – In all, 36 participants post-CTBI (mean age 21.47 years, SD=2.74), 16 males) and 18 healthy controls (mean age 20.94 years, SD=2.21), 12 males) were recruited from a larger sample of a longitudinal study conducted at the Royal Children's Hospital, Melbourne, Australia. Information about social and psychological functioning was collected via questionnaires completed at 15 years post-injury. Findings: – Results showed that post-CTBI, adolescents and young adults reported elevated risk of developing psychological problems following their transition into adulthood. CTBI survivors reported greatest problems on internalizing symptoms such as depression, anxiety and withdrawal. Social implications: – Despite the reported psychological symptoms, the survivors of CTBI did not report more social problems than their peers. Further research is needed to identify long-term social and psychological problems so that optimal intervention may be provided. Originality/value: – This is the first perspective longitudinal study investigating the young adults perspective of their long-term psychosocial outcomes following CTBI.